N6-methyladenosine RNA modification: an emerging molecule in type 2 diabetes metabolism - Zhang, Haocheng; Gu, Yan; Gang, Qiaojian; Huang, Jing; Xiao, Qian; Ha, Xiaoqin (Frontiers in Endocrinology, 2023)
Type 2 diabetes (T2D) is a metabolic disease with an increasing rate of incidence worldwide. Despite the considerable progress in the prevention and intervention, T2D and its complications cannot be reversed easily after diagnosis, thereby necessitating an in-depth investigation of the pathophysiology. In recent years, the role of epigenetics has been increasingly demonstrated in the disease, of which N6-methyladenosine (m6A) is one of the most common post-transcriptional modifications. Interestingly, patients with T2D show a low m6A abundance. Thus, a comprehensive analysis and understanding of this phenomenon would improve our understanding of the pathophysiology, as well as the search for new biomarkers and therapeutic approaches for T2D. In this review, we systematically introduced the metabolic roles of m6A modification in organs, the metabolic signaling pathways involved, and the effects of clinical drugs on T2D.